Regional Expansion as a Constitutional Notion in the Environmental Sector - H. Syafa’at Anugrah Pradana; Pikahulan, Rustam Magun (Faculty of Law, Mulawarman University, 2021)
The expansion of a new autonomous region in its regulations does not include aspects of fulfilling the environment as a requirement for regional capacity so that it contradicts one of the environmental principles, namely the principle of sustainability. Therefore, the author wants to analyze the new concept of the environment in which this concept aims to make the environment an important part or main prerequisite in terms of regional expansion. The method used in finding the legal concept of regional expansion, especially on the fulfillment of environmental aspects, is by studying and analyzing environmental philosophy and determining its meaning so that it needs to be a consideration in order to fulfill the requirements for new autonomous regions to be expanded. Regarding the legal concept of regional expansion in the environmental field, it begins with determining the environment and nature, ways to respect the environment, clarity on the moral status of animals and plants, restoration of nature, and considering environmental sustainability for future generations. Referring to the philosophical aspect, the author includes environmental aspects as a basic requirement for regional capacity in the formation of an area, especially for the expansion of preparatory areas. Thus, the existence of the environment can still be felt along with the times.